2021
DOI: 10.1016/j.ygyno.2021.08.026
|View full text |Cite
|
Sign up to set email alerts
|

From FIGO-2009 to FIGO-2018 in women with early-stage cervical cancer; Does the revised staging reflect risk groups?

Abstract: The revised FIGO-2018 system causes stage migration for a large proportion of women with early-stage cervical cancer. • Upstaging occurred in 49.8% (122/245) and downstaging to FIGO-2018 IA stages in 4.9% (12/245). • Women who were downstaged to FIGO-2018 IA stages did not have nodal metastatic disease. • The attention on depth of invasion rather than horizontal dimension seems to correctly reflect the risk of nodal metastases. • Nodal metastases which are initially identified by imaging should be histological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
(41 reference statements)
1
10
0
Order By: Relevance
“…The revised staging was proposed to allow better differentiation of prognostic outcomes and facilitate better clinical management [2]. However, this revision caused a stage migration for a large proportion of women with early stage cervical cancer [3]. Women previously staged as IB1 stage disease based on lateral extent more than 7 mm with depth of invasion < 5 mm, are now considered FIGO stage 2018 IA disease and are possibly eligible for less radical surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The revised staging was proposed to allow better differentiation of prognostic outcomes and facilitate better clinical management [2]. However, this revision caused a stage migration for a large proportion of women with early stage cervical cancer [3]. Women previously staged as IB1 stage disease based on lateral extent more than 7 mm with depth of invasion < 5 mm, are now considered FIGO stage 2018 IA disease and are possibly eligible for less radical surgery.…”
Section: Introductionmentioning
confidence: 99%
“…However, clinical trials, such as the SHAPE trial (NCT01658930), are still awaited to further guide the paradigm of treatment in patients with tumors < 2 cm horizontal width [4]. Matsuo et al validated the revised staging FIGO 2018 for stage IB and IIIC disease specifically, but further large cohort studies assessing the prognostic significance of the revised FIGO are lacking [3,5]. In addition, the new FIGO staging system, in contrast to FIGO treatment guidelines, does not incorporate other known prognostic factors, such as histopathological factors and lymph-vascular space invasion (LVSI), and therefore may not fully reflect risk groups [2,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…(2.8%) in a prospective study [20]. Likewise, in the prospective SENTICOL study, the authors found a low risk of metastases in tumours with < 10 mm depth of invasion and no LVSI (3% isolated tumour cells and 1% micrometastases) [21].…”
Section: Discussionmentioning
confidence: 81%
“…The staging criteria for the current study were adopted from the 2009 version, and clinical examination was considered as the main basis for staging. Sponholtz et al 9 reported an increase in LNM with increasing FIGO Stage, with no lymph node metastasis in Stages IA1 and IA2, but 89.47% in Stage IB1. In our study, the LNM rates were 20.1% and 27.6% for Stages I and II, respectively, similar to previous studies.…”
Section: Discussionmentioning
confidence: 98%